Quitline nurses' experiences in providing telephone‐based smoking cessation help to mental health patients: A mixed methods study - Rosa, Nathália; Feliu, Ariadna; Ballbè, Montse; Alaustre, Laura; Vilalta, Eva; Torres, Núria; Nieva, Gemma; Pla, Marga; Pinet, Cristina; Raich, Antònia; Mondon, Sílvia; Barrio, Pablo; et al. (Journal of psychiatric and mental health nursing, 2024)
Accessible Summary What is known on the subject? Quitlines are known to be effective in helping people quit smoking, including those with mental health conditions. It is particularly important to address smoking in this population as the prevalence of smoking ranges from 40% to 75%. However, professionals working in quitlines often face barriers due to their limited training and resources to effectively support these smokers quit, especially if they are not mental health professionals. Therefore, training programmes should be developed to enhance their knowledge and skills in providing smoking cessation support to this vulnerable population. What the paper adds to existing knowledge? The ‘061 QUIT‐MENTAL study’ evaluated the efficacy of a proactive telephone‐based intervention for smoking cessation among smokers with severe mental health disorders. Conducted through a quitline service in Catalonia, Spain, the study focused on training non‐mental health specialized nurses and other health professionals to provide evidence‐based interventions for promoting smoking cessation among individuals with mental health disorders. The objective of this study is to assess the changes in nurses' knowledge and readiness to treat smokers with mental health conditions, while also capturing their insights and perceptions regarding the facilitators and barriers to providing smoking cessation interventions. The training and insights of the nurses were integral to conducting this research and providing valuable information for the future sustainability of such interventions. This is particularly important as quitlines hold the potential to offer cessation support to these patients at the community level. What are the implications for practice? While the training programme was successful in improving non‐mental health specialized nurses' knowledge and motivation skills to help patients with mental health disorders quit smoking, they encountered obstacles in delivering this intervention over the phone. These difficulties were mainly due to challenges in reaching participants and delivering the intervention as detailed in the protocol. The study highlights the need of reducing barriers for providers in attending to these patients, particularly if they are non‐mental health specialized professionals. By minimizing the stigmatization associated with caring for mentally ill individuals and promoting coordination with specialists, innovative approaches may be introduced to alleviate the burden of tobacco‐related diseases among this population. Introduction The viewpoint of those who implement a programme for the first time is crucial for understanding its impact and ensuring its long‐term viability. The 061 QUIT‐MENTAL study was a pragmatic randomized controlled trial evaluating a proactive telephone‐based intervention addressed to mental health patients conducted by non‐psychiatric specialized nurses. Aim We assessed nurses' knowledge of smoking cessation interventions addressed to this population before and after receiving training and their insights after delivering the intervention. Method Mixed methods study: (1) Pre‐post evaluation to assess self‐reported knowledge, self‐efficacy and opinions about smoking cessation. (2) In‐depth interviews with key nurses to ascertain their perceptions regarding the impact of the training received in delivering the study intervention. Results The training enhanced nurses' knowledge of psychological and pharmacological resources to aid these patients, as well as their ability to increase their motivation to quit. However, nurses reported difficulties in delivering population‐based interventions to individuals with mental health disorders. These challenges primarily arose from participants being hard to reach, exhibiting low motivation to quit, struggling to comprehend instructions or follow recommendations, and nurses feeling unsure about their capacity to assist individuals with mental illnesses in quitting, despite the training they received. Discussion Despite the training and protocol designed to facilitate the delivery of the intervention, nurses faced difficulties in providing population‐based interventions to individuals with mental health disorders. Implications for Practice Future quitline programmes aimed at the population with mental health disorders should strive to reduce barriers for providers in attending to these patients, particularly if they are non‐mental health specialized professionals. By minimizing the stigmatization associated with caring for mentally ill individuals and promoting coordination with specialists, innovative approaches may be introduced to alleviate the burden of tobacco‐related diseases among this population.